IMPLEMENTASI PENDIDIKAN PROFETIK GURU AKIDAH AKHLAK DALAM MENINGKATKAN PERILAKU ISLAMI PESERTA DIDIK MA TANBIHUL GHOFILIN BANJARNEGARA - Naufal , Naufal; Dwi Kuswianto (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2022)
This study aims to determine the efforts of moral aqidah teachers in improving students’ Islamic behavior, know the obstacles of moral aqidah teachers in enhancing students’ Islamic behavior, and how to find out how to overcome the challenges of moral aqidah teachers in improving students’ Islamic behavior.This study used the descriptive qualitative method. Researchers collected data by using in-depth interviews, participant observation, and documentation. While the data analysis technique used interactive analysis, with the stages of data collection, data editing, and data presentation.The results of this study: 1) that the efforts of the aqidah moral teacher in improving the Islamic behavior of students by holding religious activities such as holding regular monthly recitations, increasing students’ awareness by living clean, setting good examples, providing classical guidance; 2) Obstacles in improving the Islamic behavior of students from environmental factors, and parents; 3) how to overcome obstacles in improving the Islamic behavior of students by giving punishment and collaborating with boarding school administrators and parents of students.